Analytical method development and validation of olmutinib bulk drug as per ICH Q2 guidelines by using RP-HPLC Method - KHANDARE, BALU; Musle, Atish C.; Arole, Sanket S.; Popalghat, Pravin V. (Journal of Drug Delivery and Therapeutics, 2019)
RP-HPLC is fast, simple, sensitive, precise, and reproducible (liquid chromatography) method, developed and validated to analyseolmutinib bulk dosage form. Using C-18 HPLC column separation was carried out. This was maintained at ambient temperature. During separation mobile phase consist of methanol (100 v/v) was delivered at a rate of 1mL/min. Using UV detector analysis was carried out at the wavelength 267.68 nm. RP-HPLC method was validated by using various parameters like, precision, limit of quantitation (LOQ), linearity and robustness. The RP-HPLC method was found to be linear over the concentration ranges from 50-100 μg/mL (r2 =0.999). Retention time for bulk olmutinib was found to be 9.349 min. LOQ of method was 5.8540 μg/mL and LOD 3.0536μg/mL. Thus, the developed RP-HPLC method was found to be robust and rugged which can be applied for the regular analysis of olmutinib in the bulk as well as pharmaceutical dosage form. Keywords: C18, RP-HPLC, Methanol, Olmutinib